2021
DOI: 10.1155/2021/6627242
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Damage Model of Coal Rock Caused by Hydraulic Pressure and Electrical Impulse in Borehole

Abstract: The purpose of this study is to study the damage and fracturing effects of high-voltage discharge on coal-rock mass under the action of hydrostatic pressure. Based on the traditional damage evolution model and the change of the effective bearing area and stress around the microcrack of coal-rock mass on a microscopic scale, the expression of macroscopic damage variation of coal-rock mass under the action of electrohydraulic coupling was derived, and its damage constitutive relation was established. The high-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Yin Zhiqiang studied the hydraulic and electrical characteristics of high voltage pulse discharge in water from the theoretical and experimental perspectives and evaluated the cracking effect of coal rock mass. Then Bao Xiankai used ultrasonic detection technology combined with a variety of advanced numerical simulation software to study the number and CT images to identify and extract cracks in coal core specimens. The parameters such as length, quantity, density, fracture rate, and fractal dimension are further used to quantitatively describe cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Yin Zhiqiang studied the hydraulic and electrical characteristics of high voltage pulse discharge in water from the theoretical and experimental perspectives and evaluated the cracking effect of coal rock mass. Then Bao Xiankai used ultrasonic detection technology combined with a variety of advanced numerical simulation software to study the number and CT images to identify and extract cracks in coal core specimens. The parameters such as length, quantity, density, fracture rate, and fractal dimension are further used to quantitatively describe cracks.…”
Section: Introductionmentioning
confidence: 99%
“…found that a higher breakdown voltage makes the coal body generate more excess pore space, which is more conducive to the extraction of CBM and coal resources . Bao et al found that hydrostatic pressure and voltage affect the effect of HVEPs to fracture coal bodies …”
Section: Introductionmentioning
confidence: 99%
“…15 Bao et al found that hydrostatic pressure and voltage affect the effect of HVEPs to fracture coal bodies. 16 The working mode of electrical pulses can be classified as electro-fracturing and electro-hydraulic fracturing depending on the medium. 17,18 Electro-fracturing is generated by a direct encounter of the electrode with the material.…”
Section: Introductionmentioning
confidence: 99%